The importance of the bank tax for the Polish state budget − has the COVID-19 pandemic reduced the proceeds from this tax? - Giżyński, Juliusz (Znaczenie podatku bankowego w budżecie państwa polskiego – czy pandemia COVID-19 obniżyła wpływy z tytułu tego podatku?, 2021)
The article’s main objective was to analyse the implications of the tax on certain financial institutions, referred to as the bank tax, for the Polish state budget since the very beginning of the levy. The article also indicates the essence and the purpose of this tax’s functioning, in comparison to the European Union countries, as well as presents the principles of its legal structure. Based on the research carried out, it was found that the level of the bank tax contributions to the state budget in 2016-2019 was stable, assuming a slight upward trend that continued in 2020, despite the outbreak of the COVID-19 pandemic. The Polish government’s additional financial activities, induced by the pandemic, have increased the tax base in the bank levy. These activities have also contributed to the strengthening of the links between the government and the banking sectors, measured by the sovereign-bank nexus index, as a result of the continued increase in the banks’ exposure to Treasury securities. These securities are excluded from the bank-levy tax base. The following research method was used in the preparation of the article: a critical study of the literature and an analysis of the empirical data published by the Polish Financial Supervision Authority, the Ministry of Finance, the Supreme Audit Office, and the National Bank of Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 4, s. 55-76
Keywords: bank tax; state budget; coronavirus crisis; COVID-19; podatek bankowy; budżet państwa; kryzys koronawirusowy